Living and Learning with Technology: Faculty as Reflective Practitioners in the Online Classroom - Patricia A. Lawler; Kathleen P. King; Stephen C. Wilhite Widener University (Adult Education Research Conference, 2004)
This qualitative study examined the experiences of 11 faculty members who have been involved in online instruction. The goal was to explore how assuming the role of adult learners in developing online courses contributed to their becoming critically reflective about their instructional practices. Faculty interviews revealed engagement in critical reflection and were used to suggest strategies for faculty development that could further support such perspectives and practice.